Biological and molecular characterization of tomato spotted wilt virus (TSWV) resistance‐breaking isolates from Argentina. (3rd October 2019) - Ferrand, L.; Almeida, M. M. S.; Orílio, A. F.; Dal Bó, E.; Resende, R. O.; García, M. L.
Abstract : Tomato spotted wilt virus (TSWV) has been present in Argentina since 1938 and had limited sweet pepper and tomato production until the introduction of resistant cultivars bearing Tsw and Sw‐5b genes. However, the wide use of TSWV‐resistant pepper plants in La Plata Horticultural Belt (LPHB) triggered the emergence of resistance‐breaking isolates (RB), increasing the economic impact of TSWV in pepper. This work characterized 11 natural RB pepper isolates from LPHB that have overcome the Tsw resistance gene in Capsicum sp. but are unable to break the Sw‐5b ‐mediated resistance in tomato. Phylogenetic analysis of the N gene showed that the LPHB isolates are most closely related to isolates from Asia, indicating that Argentine TSWV isolates might have emerged from the Asian continent. The NSs sequence analysis reinforces the hypothesis that the appearance of an RB phenotype is a consequence of a number of different single amino acid substitutions spread along the NSs gene that lead to multiple independent evolutionary events. These results provide information on the current situation of the tospovirus–pepper/tomato pathosystems in LPHB, which represents a fundamental prerequisite to include these RB isolates in future screening programmes in order to select new and durable sources of resistance to TSWV in pepper.